2012
DOI: 10.1016/j.neuropharm.2011.07.043
|View full text |Cite
|
Sign up to set email alerts
|

Is treatment-resistance in unipolar melancholic depression characterized by decreased serotonin2A receptors in the dorsal prefrontal – Anterior cingulate cortex?

Abstract: Objectives: Quite a number of patients diagnosed with major depression are resistant to several well carried-out psychopharmacological interventions. It remains unclear as to how the serotonergic system is implicated in the phenomenon of treatment-resistance. regulated. However, whether this assumed underlying pathophysiological mechanism is due solely to abnormalities in the serotonergic system remains to be answered.3

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 43 publications
0
14
1
Order By: Relevance
“…Altered serotonergic function, such as decreased post-synaptic 5-HT-2A receptors in the dorsal regions of the prefrontal and the anterior cingulate cortex, were observed in antidepressant-free TRD patients (Baeken et al 2012). However, the results of the present study show no differences between patients with and without TRD in the frequency of components of MetS, BMI and both atherogenic index 1 and 2.…”
Section: Discussioncontrasting
confidence: 72%
“…Altered serotonergic function, such as decreased post-synaptic 5-HT-2A receptors in the dorsal regions of the prefrontal and the anterior cingulate cortex, were observed in antidepressant-free TRD patients (Baeken et al 2012). However, the results of the present study show no differences between patients with and without TRD in the frequency of components of MetS, BMI and both atherogenic index 1 and 2.…”
Section: Discussioncontrasting
confidence: 72%
“…Among individuals with depression, suicidality has been shown to be associated with greater feelings of desperation (Garlow et al, 2008) and hopelessness (Nyer et al, 2013). Prior studies have also shown that there are structural dACC differences in MDD patients who are and are not at risk for suicide (Wagner et al, 2011), and that dACC functioning is associated with treatment-resistant depression (Baeken et al, 2012). Taken together, it is possible that specific subgroups of depressed individuals, namely those with suicidality, evidence abnormal dACC reactivity and experience the greatest affective conflict during reward anticipation due to the fact that the context is starkly incongruent with their hopeless and/or pessimistic mood.…”
Section: Discussionmentioning
confidence: 99%
“…In a study using the radioligand 123 I-5-I-R91150 with single photon emission computed tomography in TRD patients, it could be demonstrated that the postsynaptic serotonin 5-HT 2A receptors in dorsal regions of the prefrontal and the ACC are down-regulated compared to never depressed controls, whereas 5-HT 2A receptor binding did not differ from controls in first-episode depressed patients (Baeken, De Raedt & Bossuyt, 2012). Based on these findings, the effect of 10 daily weekday HF-rTMS sessions applied to the left DLPFC on postsynaptic 5-HT 2A receptor binding indices was examined in a group of antidepressant-free, pharmaco-resistant depressed (TRD) patients .…”
Section: Molecular Approach To Working Mechanisms Of Neurostimulationmentioning
confidence: 99%